Selective lesion of retrotrapezoid Phox2b-expressing neurons raises the apnoeic threshold in rats - Takakura, Ana C (Blackwell Science Inc, 2008)
Injection of the neurotoxin saporin–substance P (SSP-SAP) into the retrotrapezoid nucleus (RTN) attenuates the central chemoreflex in rats. Here we ask whether these deficits are caused by the destruction of a specific type of interneuron that expresses the transcription factor Phox2b and is non-catecholaminergic (Phox2b(+)TH(−)). We show that RTN contains around 2100 Phox2b(+)TH(−) cells. Injections of SSP-SAP into RTN destroyed Phox2b(+)TH(−) neurons but spared facial motoneurons, catecholaminergic and serotonergic neurons and the ventral respiratory column caudal to the facial motor nucleus. Two weeks after SSP-SAP, the apnoeic threshold measured under anaesthesia was unchanged when fewer than 57% of the Phox2b(+)TH(−) neurons were destroyed. However, destruction of 70 ± 3.5% of these cells was associated with a dramatic rise of the apnoeic threshold (from 5.6 to 7.9% end-expiratory [Image: see text]). In anaesthetized rats with unilateral lesions of around 70% of the Phox2b(+)TH(−) neurons, acute inhibition of the contralateral intact RTN with muscimol instantly eliminated phrenic nerve discharge (PND) but normal PND could usually be elicited by strong peripheral chemoreceptor stimulation (8/12 rats). Muscimol had no effect in rats with an intact contralateral RTN. In conclusion, the destruction of the Phox2b(+)TH(−) neurons is a plausible cause of the respiratory deficits caused by injection of SSP-SAP into RTN. Two weeks after toxin injection, 70% of these cells must be killed to cause a severe attenuation of the central chemoreflex under anaesthesia. The loss of an even greater percentage of these cells would presumably be required to produce significant breathing deficits in the awake state.